A quantitative 14-3-3 interaction screen connects the nuclear exosome targeting complex to the DNA damage response - Blasius, Melanie; Wagner, Sebastian A; Choudhary, Chunaram; Bartek, Jiri; Jackson, Stephen P (Genes & development, 2014)
RNA metabolism is altered following DNA damage, but the underlying mechanisms are not well understood. Through a 14-3-3 interaction screen for DNA damage-induced protein interactions in human cells, we identified protein complexes connected to RNA biology. These include the nuclear exosome targeting (NEXT) complex that regulates turnover of noncoding RNAs termed promoter upstream transcripts (PROMPTs). We show that the NEXT subunit RBM7 is phosphorylated upon DNA damage by the MAPKAPK2 kinase and establish that this mediates 14-3-3 binding and decreases PROMPT binding. These findings and our observation that cells lacking RBM7 display DNA damage hypersensitivity link PROMPT turnover to the DNA damage response.
Keywords: Phosphorylation; Humans; fosforylace; Protein Binding; intracelulární signální peptidy a proteiny; MAPKAPK2; protein-serin-threoninkinasy; lidé; Exosome Multienzyme Ribonuclease Complex; nekódující RNA; ultrafialové záření; UV; proteiny 14-3-3; RNA, Untranslated; DNA damage response; Intracellular Signaling Peptides and Proteins; Protein Serine-Threonine Kinases; exozom; 14-3-3 Proteins; vazba proteinů; 14-3-3; MAP Kinase Signaling System; poškození DNA; DNA Damage; Ultraviolet Rays; nuclear exosome; MAP kinasový signální systém